Translation Strategies Applied in the Information Boards of Malukat Temple in Gianyar, Bali: A Study of Linguistics Landscape - Ni Putu Meri Dewi Pendit; Afriliani Afriliani; Ni Made Verayanti Utami (Universitas Muhammadiyah Semarang, 2023)
This study aims to describe the syntactic scope of information boards found in self-cleaning (Malukat) temples in Gianyar, Bali. In addition, this study also examines the translation strategies of bilingual information boards (Indonesian and English). The method used in this research is a qualitative approach in order to describe the syntactic scope and translation strategies on the data in found in Tirta Empul Temple. The data analysis applies the theory of landscape linguistics proposed by Yendra and Artawa (2020) and is supported by several micro linguistics theories, as follows: 1) syntactic scope theory by Noortyani (2017), 2) translation strategy theory by Molina and Albir (2002), and 3) translation equivalence theory by Nida (2000). The results of this study show that the information boards in the temples have various syntactic scopes, namely in the form of phrases and sentences. However, it is dominantly found in the form of sentences. It is because the information conveyed on the boards is more detail and clearly presented so that they are easily understood by visitors. Meanwhile, the translation strategy of the public space signboard uses calque, literal, established equivalent, and reduction strategies. The literal translation strategy dominantly used on the public signs at the temples because it is easier to understand since it is translated word per word.